Dermatomyositis-Related Nonischemic Central Retinal Vein Occlusion. Issue 3 (September 2015) - Wang, Yvonne; Morgan, Michael L.; Espino Barros Palau, Angelina; Lee, Andrew G.; Foroozan, Rod
Abstract : Abstract: A 25-year-old woman with dermatomyositis suffered a right central retinal vein occlusion (CRVO) with visual acuity of 20/40. Examination of the right eye showed vitreous cells, suggesting inflammation of the central retinal vein leading to a CRVO as the presumed mechanism. She was admitted to hospital, and extensive evaluation was negative. She was maintained on corticosteroids to manage her dermatomyositis. One month later, she had macular edema and elevated intraocular pressure. Both resolved with dorzolamide, timolol, and intravitreal bevacizumab, and vision returned to 20/20 in the right eye.